Xpert MTB/RIF Ultra versus Xpert MTB/RIF for the diagnosis of tuberculous meningitis: a prospective, randomised, diagnostic accuracy study - Donovan, J; Thu, DDA; Phu, NH; Dung, VTM; Quang, TP; Nghia, HDT; Trinh, DHK; Geskus, RB; Tan, LV; Thuong, NTT; Thwaites, G (Elsevier, 2020)
Background: Xpert MTB/RIF Ultra (Xpert Ultra) might have higher sensitivity than its predecessor, Xpert MTB/RIF (Xpert), but its role in tuberculous meningitis diagnosis is uncertain. We aimed to compare Xpert Ultra with Xpert for the diagnosis of tuberculous meningitis in HIV-uninfected and HIV-infected adults.